2023
DOI: 10.1002/cphc.202300272
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Kramers’ Theory of Reaction Rates

Abstract: In this short review, we provide an update of recent developments in Kramers’ theory of reaction rates. After a brief introduction stressing the importance of this theory initially developed for chemical reactions, we briefly present the main theoretical formalism starting from the generalized Langevin equation and continue by showing the main points of the modern Pollak, Grabert and Hänggi theory. Kramers’ theory is then sketched for quantum and classical surface diffusion. As an illustration the surface diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…As such, long jumps replace a single jump in the atomistic picture and while the total number of jumps follows an exponential increase with temperature, the occurrence of particular jump types does not. For single atom diffusion, long jumps become clearly more important as the temperature increases ( Braun and Ferrando, 2002 ; Pollak and Miret-Artés, 2023 ) and it has also been suggested that these are a general feature of hydrogen diffusion on close-packed transition metal surfaces at high temperatures ( Townsend and Avidor, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…As such, long jumps replace a single jump in the atomistic picture and while the total number of jumps follows an exponential increase with temperature, the occurrence of particular jump types does not. For single atom diffusion, long jumps become clearly more important as the temperature increases ( Braun and Ferrando, 2002 ; Pollak and Miret-Artés, 2023 ) and it has also been suggested that these are a general feature of hydrogen diffusion on close-packed transition metal surfaces at high temperatures ( Townsend and Avidor, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a matter of fact, when we study the out-of-equilibrium dynamics, the representation based on the sequence of basins and spin discrete variables is not sufficient since the relaxation times of the system depend on the energy barriers between the potential wells [61,98]. This is consistent, e.g., with the Kramers rate formula, originally formulated to deal with chemical reaction rates [99][100][101][102][103]. The consideration of the possible rate effects is particularly important when the stretching of the macromolecular chains, or other nanosystems, is performed with a large traction velocity [104,105].…”
Section: Introductionmentioning
confidence: 94%